The Effect of Online Games on the Emotions of Junior High School Students - Tarissa Ardhana Hajizah; Eva Marsepa; Siti Haeriyah (Jurnal Pendidikan Indonesia Gemilang, 2024)
Indonesia is one of the biggest gaming markets in the world. Most mobile or video games are played via mobile phones, tablets, or consoles. According to a data report from We Are Social, Indonesia is a country with the third largest number of video game players in the world, 94.5%. This study aimed to discover more about the influence of online games on adolescent emotions at one of the junior high schools in Sepatan, Tangerang, Indonesia. The research design used in this study is a quantitative approach with a correlational design. The sampling technique used in this study was purposive sampling. The sample used amounted to 172 respondents. The data analysis used in this study is Kendall's tau-b correlation test, which looks at the correlation coefficient value. The results of this study show that students' use of online games is in the moderate category (76.7%), and emotions are in the low category (65.1%). In the statistical test results obtained, p.value = 0.000 ≤ 0.05. Therefore, it can be concluded that online games significantly influence adolescent emotions.